Counting the cost of drought induced productivity losses in an agro-based economy: The case of Uganda - Kilimani, Nicholas; Heerden, Jan van; Bohlmann, Heinrich; Roos, Louise (Economic Research Southern Africa (ERSA), 2016)
Climate variability can affect economies directly through its impact on agricultural output, and indirectly, through its effect on the activi- ties of down-stream industries and household welfare. This paper uses a Computable General Equilibrium model with a disaggregated agricultural sector to analyse the impact of a drought on the Ugandan economy. The losses were assessed with respect to GDP, agricultural output, employ- ment, the trade balance and household consumption. The drought effects were shown to vary by sector. The fall in employment within the agricul- tural industries was less compared to the output losses. At a macro level, exports declined, while at a household level, the terms of trade gains mit- igated part of the potential welfare losses thereby reducing consumption, but to a lesser degree. The findings indicate that a drought can cause substantial losses to the economy. The need for targeted interventions to mitigate such drought impacts is therefore critical.
Keywords: Computable general equlibrium modelling; Drought; Eco- nomic activity